2014
DOI: 10.2147/ijn.s71625
|View full text |Cite
|
Sign up to set email alerts
|

Surface characteristics of and in vitro behavior of osteoblast-like cells on titanium with nanotopography prepared by high-energy shot peening

Abstract: Background and methods Commercial pure titanium with nanotopography was prepared via a high-energy shot-peening (HESP) technique. The surface characteristics were evaluated, and the preliminary cell responses to the nanotopographical surface were investigated. Results The nanotopographical surface layer on titanium was successfully processed by HESP. The average nanoscale grains were approximately 60 nm in diameter and they were nonhomogeneously distributed on the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…x 10 -3 µA/cm 2 , while the average E corr values were found to be -0.28 V and -0.12 V. The reduc on in I corr values and increase in E corr values clearly show an improvement in corrosion resistance a�er SMAT. This type of behaviour had been reported previously for SMAT-processed cp-Ti [15], Ti-6Al-4V alloy [16] and β Ti-25Nb-3Mo-3Zr-2Sn alloy [18]. It has been proposed in the literature that severe plas c deforma on methods like SMAT leads to genera on of large number of la ce defects, as also seen from the microstructure of SMAT sample in the present alloy.…”
Section: Corrosion Studiessupporting
confidence: 88%
See 1 more Smart Citation
“…x 10 -3 µA/cm 2 , while the average E corr values were found to be -0.28 V and -0.12 V. The reduc on in I corr values and increase in E corr values clearly show an improvement in corrosion resistance a�er SMAT. This type of behaviour had been reported previously for SMAT-processed cp-Ti [15], Ti-6Al-4V alloy [16] and β Ti-25Nb-3Mo-3Zr-2Sn alloy [18]. It has been proposed in the literature that severe plas c deforma on methods like SMAT leads to genera on of large number of la ce defects, as also seen from the microstructure of SMAT sample in the present alloy.…”
Section: Corrosion Studiessupporting
confidence: 88%
“…The process have been found to enhance the fa gue life by delaying crack ini a on on the surface due to increase in the hardness and introducing compressive residual stresses [15]. In addi on, there are reports on improvement in cell a�achment and prolifera on on several systems [16,17].…”
Section: Introduc Onmentioning
confidence: 99%
“…In this sense, it is known that the surface topography of an alloy can influence cell adhesion, and thus cell proliferation and differentiation [ 11 , 27 , 28 ]. It has been reported that nanorough surfaces provide better cell proliferation and differentiation than smooth ones [ 17 ], even though other authors reported that better results are obtained with microrough surfaces [ 28 ]. A drawback for standardizing the knowledge on the importance of topography on cell behaviour is the lack of consensus for surface topography characterization [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been described that differentiation of human primary osteoblasts is enhanced by nanostructured superimposed onto micro-rough Ti-6Al-4V surfaces [ 34 ]. Similarly, Deng et al concluded that nanostructured Ti is beneficial for MG63 osteosarcoma cells adhesion, viability and differentiation [ 17 ]. In contrast with all these previous reports, our study with Saos-2 cell line shows no significant differences in terms of cell viability, proliferation and differentiation among the three types of evaluated surfaces neither for the Ti-6Al-4V alloy, nor for the TiZrCuPd.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation